2017
DOI: 10.1108/ssmt-04-2016-0007
|View full text |Cite
|
Sign up to set email alerts
|

Geometric size effect on IMC growth and elements diffusion in Cu/Sn/Cu solder joints

Abstract: Purpose The purpose of this paper is to investigate the effect of geometric size on intermetallic compound (IMC) growth and elements diffusion of Cu/Sn/Cu solder joint and establish the correlation model between the thickness of the IMC layer and size of the solder joint on the dozens of microns scale. Design/methodology/approach The sandwich-structured Cu/Sn/Cu solder joints with different gaps between two copper-clad plates (δ) are fabricated using a reflow process. The microstructure and composition of so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 15 publications
(18 reference statements)
0
2
0
Order By: Relevance
“…In lead-free solder joints of microelectronic packaging, Kirkendall voids are often found in Cu 3 Sn intermetallic compound (IMC) near the interface between Cu 3 Sn and Cu after annealing (Gao et al, 2008;Zeng and Tu, 2002;Chan et al, 2013;Zhu and Sun, 2017). Figure 1 is an anin-situ scanning electron microscopy (SEM) photograph of interfacial microstructure between a Cu/Sn/Cu system during isothermal annealing (Park et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…In lead-free solder joints of microelectronic packaging, Kirkendall voids are often found in Cu 3 Sn intermetallic compound (IMC) near the interface between Cu 3 Sn and Cu after annealing (Gao et al, 2008;Zeng and Tu, 2002;Chan et al, 2013;Zhu and Sun, 2017). Figure 1 is an anin-situ scanning electron microscopy (SEM) photograph of interfacial microstructure between a Cu/Sn/Cu system during isothermal annealing (Park et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, a coating of Ni over the Cu metallization is often used as a diffusion barrier (Chan et al, 2002). Studies have been reported on the reaction of different solders with Cu substrates (Ju et al, 2014;Zhu and Sun, 2017;Bi et al, 2012;Yan et al, 2016) and Ni/Cu substrates during reflow and ageing (Huang and Lin, 2004;Lee et al, 2005;Mittal and Lin, 2012;Mittal and Lin 2014;Tian et al, 2003). Reaction of Sn-Ag, Sn-Cu and Sn-Bi solders with Ni substrates leads to the formation of Ni 3 Sn 4 IMC, whereas the Sn-Zn solder alloy reacts with Ni to form the Ni 19 Zn 80 Sn IMC (Chan et al, 2002).…”
Section: Introductionmentioning
confidence: 99%